Influencer : the new science of leading change - Grenny, Joseph (McGraw-Hill Education, 2013)
Combining the remarkable insights of behavioral scientists and business leaders with the astonishing stories of high-powered influencers from all walks of life; this book presents robust strategies for making change inevitable in your personal life; your business; and your world. --